Reflective Practice in the Growth of an Effective EFL Teacher: An Autoethnography - Dutta, Krishna (Journal of NELTA, 2025)
Reflective practice aims to aid the growth of any teacher while pursuing their career as a target language teacher. The study generated initial themes on the different phenomenal impacts of reflective practice on teaching second language and solving issues in the EFL classrooms. Then my accounts as a student of teacher education mirrored the reinforcement of motivation, teacher identity, and resilience while addressing my classroom puzzles. Finally, the article divulged the contributions of reflection in teaching target language, critically analyzing the researcher’s personal experience of everyday challenges of teaching a second language and interpreting its connection to the learning outcomes of the learners and myself as an EFL teacher. To bring this insider knowledge of the teachers in Bangladeshi EFL classrooms, the research used Autoethnography as a qualitative research method, where the researcher became the participant, recording the self-narratives over two years during the master’s degree in English Language Education, particularly six months of teacher development and six months of Action Research. Thus, my paper envisions the topic of teachers’ reflective practices for wider reach, contributing not only to the development of a teaching pedagogy but also to the incorporation of Reflective Practice in the education of teachers’ professional programs.